ADDRESS SEQUENCES FOR MULTI RUN RAM TESTING - V. N. Yarmolik; S. V. Yarmolik (Informatika)
A universal approach for generation of address sequences with specified properties is proposed and analyzed. A modified version of the Antonov and Saleev algorithm for Sobol sequences genera-tion is chosen as a mathematical description of the proposed method. Within the framework of the proposed universal approach, the Sobol sequences form a subset of the address sequences. Other sub-sets are also formed, which are Gray sequences, anti-Gray sequences, counter sequences and sequenc-es with specified properties.